Analysis of free state land plots in the Republic of Lithuania - Abalikstiene, E., Kaunas College of Forestry and Environmental Engineering (Lithuania) (Latvia University of Agriculture, 2008)
Lithuanian agriculture is based on the non-competitive, small-sized farms. With the possibilities to use land of agricultural effectively and develop competitive agribusiness, while establishing conditions to developing rationally managed land-owning, sales of free state land of agricultural purposes are very closely connected. The subject of research - free state land. The purpose of research is to analyze free state land in Lithuania. To complete this analysis 51 district municipalities have been selected. Located in the cities free state land wasn't analyzed. After the analysis was performed, it was determinate, that the biggest amount of free state land remains in Vilnius county, and the smallest amount - in Marijampole county.